(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Eagle’s syndrome represent as a neck, cervicofacial pain, dysphagia, facial pain, globus sensation, tinnitus, otalgia and headache, it may be unilateral or bilateral. About 4% of adult population accounted elongated styloid process, which are the principal factor of Eagle’s syndrome and followed by 0.16% of patients are symptomatic. Stylohyoid ligament calcification is the second most common factor. The diagnosis must be made through a detailed history, clinical examination, and various imaging modalities. A 36 years old female patient presented with persistent pain in the throat. An elongated styloid process was diagnosed and was removed by transoral approach following the patient was relieved from her symptoms. J Bangladesh Coll Phys Surg 2022; 40: 72-74